The Laws of Maryland, with the Charter, the Bill Of Rights, the Constitution of the State, and Its Alterations, the Declaration of Independence, and the Constitution of the United States, and Its Amendments, at 465 (1811) - (:unkn) unknown (General Publisher, 1811)
Prohibited the carrying of any pistol, hanger, cutlass, bludgeon, or other offensive weapon with the intent to assault a person. Punishable by imprisonment for 3 months to 2 years.
--
Keywords: CARRY - INTENT TO COMMIT CRIME